2000
DOI: 10.20870/oeno-one.2000.34.2.1011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different plastic sheet coverings on microclimate and berry ripening of table grape cv "Matilde"

Abstract: Two types of plastic cover (LDPE + EVA and LDPE + HDPE) were tested to assess their radiometric properties and the influence on the vegetative and reproductive performances of 'Matilde' table grape. Films showed the same transmittance to short infrared waves, but LDPE + EVA had a higher transmissivity to visible, PAR and short infrared wavelength ranges of solar radiation, especially as for the « direct » light component. In comparison to the open field, covering increased GDD accumulation and advanced budbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 3 publications
2
21
1
3
Order By: Relevance
“…Also Phadung et al (2005) who worked on 'Perlette' grape, results showed that plastic mulching (on soil) increased yield. The results were in disagreement with Novello et al (2000) who showed that yield per vine increased under low density polyethylene + ethylvinyl acetate (LDPE+EVA). Furthermore, Rodriguez-Lovelle et al (2000) showed that grape yields were lower with grass cover.…”
Section: Yieldcontrasting
confidence: 87%
See 1 more Smart Citation
“…Also Phadung et al (2005) who worked on 'Perlette' grape, results showed that plastic mulching (on soil) increased yield. The results were in disagreement with Novello et al (2000) who showed that yield per vine increased under low density polyethylene + ethylvinyl acetate (LDPE+EVA). Furthermore, Rodriguez-Lovelle et al (2000) showed that grape yields were lower with grass cover.…”
Section: Yieldcontrasting
confidence: 87%
“…It can be concluded from the above data that, all treatments increased significantly cluster weight during the two seasons compared with control treatment which gave the lowest value but in the second season the treatments (P1WSCS) and (P1YSCS) were similar to control treatment. This finding might gain support from the work previously done by Novello et al (2000), Shrestha et al (2000) and Phadung et al (2005) who showed that plastic mulching increased fruit weight more than no mulching but fruit cluster weight was not affected by mulching treatments.…”
Section: Number Of Berries /Clustersupporting
confidence: 83%
“…For no-sleeve and sleeve treatment means, respectively, n = 16 and 48 at Vin 1 and Paradise, and n = 12 and 36 at Dark Horse. Polyethylene enclosures constructed around large blocks of vines have been used successfully to trap solar energy and induce early budbreak, veraison and maturation of table grapes (Novello et al 1999(Novello et al , 2000. Wavelength-selective polyethylene mulch applied in the planted row, and clear polyethylene enclosures (sleeves) constructed around vine cordons or canes are also effective in trapping solar energy to increase soil and canopy microclimate temperatures (Bowen et al 2004).…”
mentioning
confidence: 99%
“…1). The radiometric properties of plastic covers can affect canopy microclimate (Novello et al, 2000), but there is a lack of knowledge on the effects that covers used in California may have on canopy microclimate, yield, and fruit quality. Other grape-growing countries, particularly Italy, also use plastic covers, but the timing and method of deployment, and materials used are quite different (Novello and de Palma, 2008).…”
mentioning
confidence: 99%
“…Other grape-growing countries, particularly Italy, also use plastic covers, but the timing and method of deployment, and materials used are quite different (Novello and de Palma, 2008). In Italy and some other countries, plastic sheets may be used as a form of protected cultivation, in which the plastic forms a roof and walls around the vineyard (Novello and de Palma, 2008;Novello et al, 2000). Such systems may be installed in winter and kept in place until bloom to promote early ripening (Novello et al, 1999(Novello et al, , 2000.…”
mentioning
confidence: 99%